Teaching techniques to improve english pronunciation to students in the third year of elementary school at the Manuelita Sáenz school in the period of 2021-2022 - Castro Pérez, Ariana Vanessa (2021)
This research is based on the use of Sound-Color chart and Drilling techniques to improve the pronunciation skills of third grade students in order to strengthen and improve the ways in which teachers teach this essential skill for proper communication. There are teachers who, despite having a degree in English, do not know how to teach or correct their students' English pronunciation skills through technical methods and techniques. In addition, most students are not exposed to English on a consistent basis so that they can naturally learn or improve their pronunciation. However, this work is done in order to improve a skill, although not considered as one of the main skills, such as pronunciation, through teaching techniques such as the Sound-Color chart and Drilling. This proposal seeks to improve the skill of pronunciation through activities and repetitions, first training the teachers to know each technique and then they put into practice some exercises, according to the needs of the students.